Improved survival in overweight and obese patients with aggressive B-cell lymphoma treated with rituximab-containing chemotherapy for curative intent. Issue 6 (12th May 2019) - Stevenson, James K. R.; Qiao, Yao; Chan, Kelvin K. W.; Beca, Jaclyn; Isaranuwatchai, Wanrudee; Guo, Helen; Schwartz, Deborah; Arias, Jessica; Gavura, Scott; Dai, Wei Fang; Kouroukis, C. Tom; Cheung, Matthew C.
Abstract: The association between obesity and survival in non-Hodgkin lymphoma is unclear. Using the Ontario Cancer Registry we conducted a retrospective analysis of incident cases of aggressive-histology B-cell lymphoma treated with a rituximab-containing regimen with curative intent between 2008–2016. 6246 patients were included. On multivariable analysis the rate of all-cause mortality was lower for the overweight body mass index (BMI 25–29.9 kg/m 2 ) (HR 0.85; 95%CI 0.77–0.95) and obese BMI (≥30 kg/m 2 ) (HR 0.75; 95%CI 0.67–0.85) groups compared to the normal weight group (18.5–24.9 kg/m 2 ). Binomial logistic regression analysis revealed a lower odds ratio (OR) of admission to hospital during treatment in the overweight (OR 0.84; 95%CI 0.75–0.95) compared to normal weight BMI group. In the largest cohort to date of aggressive-histology B-cell lymphoma patients treated with rituximab, increased BMI is associated with a survival advantage, and the magnitude of this effect increases from overweight to obese BMI.